Migration and crime in Moscow: reality and representation - Tatyana N. Yudina; Tatiana M. Bormotova (Наука. Культура. Общество, 2022)
Authors of the article showed the close interrelationship between migration and crime, the necessity of scientific studies about this relationship. The article is written on the juxtaposition of statistics from official sources of the Ministry of internal Affairs and the populist opinion of Muscovites about the level of migration crime in the Moscow metropolis, the pros and cons of migration for the metropolis, the types of migration crimes committed by migrants, as well as the image of a migrant criminal.